2011
DOI: 10.1002/jccs.201190012
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Solid Phase Dispersion‐Accelerated Solvent Extraction for Determination of OCP Residues in Fish Muscles

Abstract: A rapid, sensitive and accurate matrix solid phase dispersion-accelerated solvent extraction (MSPD-ASE) method for selective determination of sixteen organochlorine pesticide (OCP) residues in fish samples has been developed and validated. 2 g fresh fish muscle was dispersed with 10 g anhydrous sodium sulfate and 2 g acid alumina thoroughly, and loaded into the stainless-steel extraction cell containing 6 g of acid alumina and 10 g anhydrous sodium sulfate. The temperature 60°C and two extraction cycles of 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Results showed that 1:1 (the lowest level) was the best ratio. This result is similar to the one reported by Shen et al [47] who found a 1:1 ratio by employing MSPD for the extraction of organochlorine pesticides from fish samples and determination by GC-ECD and GC-MS. Recoveries ranged from 82 to 106 % with RSD lower than 6 %. The same ratio was not verified by Fan et al [48] who concluded that a 1:3 ratio showed the best results for the extraction of steroid hormones from animal-origin food with determination by LC-MS/MS.…”
Section: Fraction Factorial Designsupporting
confidence: 93%
“…Results showed that 1:1 (the lowest level) was the best ratio. This result is similar to the one reported by Shen et al [47] who found a 1:1 ratio by employing MSPD for the extraction of organochlorine pesticides from fish samples and determination by GC-ECD and GC-MS. Recoveries ranged from 82 to 106 % with RSD lower than 6 %. The same ratio was not verified by Fan et al [48] who concluded that a 1:3 ratio showed the best results for the extraction of steroid hormones from animal-origin food with determination by LC-MS/MS.…”
Section: Fraction Factorial Designsupporting
confidence: 93%
“…This is while it was reported that addition A c c e p t e d M a n u s c r i p t 9 of NaCl decreases the efficiency of dispersion of extraction phase and mass transfer in aqueous medium, leading to a decrease in extraction efficiency. To investigate the influence of salt addition on performance of SUPRASF extraction, various experiments were performed by adding different amounts of NaCl (0-20% w/v) to the sample solution.…”
Section: Optimization Of Supramolecular Solvent Microextractionmentioning
confidence: 72%
“…Also, owing to the fact that sorbents are nonselective, further purification of the extracts is often still required to remove coextractants before further analysis. Shen et al reported combination of MSPD with accelerated solvent extraction (ASE) from soil samples and fish muscle for determination of OCP residues [9,10]. However, the consumption of hazardous organic solvents in ASE is relatively high, the final extract needs solvent evaporation; and extraction of other matrix interferences is probable, which reduces higher purification of extract.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The sample preparation for extraction is simple and rapid, the high pressure during extraction allows the recovery of thermally labile analytes even at high temperatures and numerous samples can be extracted in one cycle. Extract clean-up is usually necessary due to one major drawback of the method-the presence of a large amount of coextracted interferences which must be separated from analytes, or chromatographic performance will seriously deteriorate (Shen et al, 2011).…”
Section: Extraction Techniquesmentioning
confidence: 99%